Pelatihan Pengolahan Sampah Perkotaan Bagi Mahasiswa : Urban Waste Management Training for Students - Nining Haslida; Marini Marini; Ali Anas (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
This article aims to describe waste management training for students, especially students of the FISIP Administration Study Program, Bosowa University Makassar. In addition, this training also introduces various alternatives for students in finding alternative solutions in overcoming problems around their environment (urban) which is surrounded by garbage as well as training their sensitivity to the environment. This paper uses a quantitative research method with a sample of 50 students with a total sampling technique. Data collection techniques using questionnaires, observations, and documentation studies. The data analysis technique used is frequency and percentage tabulation. The results of the study were obtained as follows: (1) introducing waste processing techniques through the introduction of concepts and theories and their types. (2) waste management practices in which each training participant practices waste processing techniques using tools. The recommendation for this service is that it is necessary to conduct training and involvement of environmental watchdog institutions in managing urban waste